Potential mutagenicity of aflatoxin B1 in Egyptian spices - Basma El Geoshi; Gehan El-Akabawy; Mohammed El Metwally; Magda I. Soliman (BMC Genomics)
Abstract The current study aimed to detect the mutagenic impacts of aflatoxin B1 (AFB1), which is produced by Aspergillus group fungi, via a high-plant genotoxicity test. Different durations of treatment (3 h, 6 h, and 12 h) were used to treat the Vicia faba root tips with varying concentrations of Aflatoxin B1 (AFB1) following the approved protocol for plant assays published by the International Program on Chemical Safety (IPCS) and the World Health Organization (WHO). The data obtained indicated that AFB1 not only has the ability to induce various alterations in the process of mitosis, ranging from increasing to decreasing mitotic and phase indices but also leads to many mitotic aberrations. The abnormalities observed varied on the basis of the ratio of AFB1 to treatment time. The aberrations included micronuclei in interphase, stickiness; two groups ring star disturbed and oblique metaphase late separation diagonal bridge and laggard and disturbed. anaphase and telophase. This study showed that biomonitoring Vicia faba is a sustainable method for estimating the cytotoxicity and genotoxicity of applied AFB1. Additionally, AFB1 caused changes in the protein profile detected by SDS‒PAGE, with each treated sample displaying a unique electrophoretic pattern due to the formation and disappearance of certain bands. The ISSR and RAPD assays changes in band numbers in all samples compared with the untreated control, and a decrease in genetic template stability (GTS) ratios was observed with higher levels of AFB1. The image cytometric data revealed a correlation between the dosage of AFB1 and its impact on cell cycle components in the meristematic cells of Vicia faba roots. Furthermore, an increase in AFB1 concentrationled to a decrease in B-cell lymphoma 2 (Bcl2) levels, an increase in chromatin condensation levels, and an increase in poly ADP‒ribose polymorphism (PARP) levels.